2007
DOI: 10.1016/j.taap.2006.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein kinase C and disruption of endothelial monolayer integrity by sodium arsenite—Potential mechanism in the development of atherosclerosis

Abstract: Arsenic exposure has been shown to exacerbate atherosclerosis, beginning with activation of the endothelium that lines the vessel wall. Endothelial barrier integrity is maintained by proteins of the adherens junction (AJ) such as vascular endothelial cadherin (VE-cadherin) and β-catenin and their association with the actin cytoskeleton. In the present study, human aortic endothelial cells (HAECs) were exposed to 1, 5 and 10 μM sodium arsenite [As(III)] for 1, 6, 12 and 24 h, and the effects on endothelial barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
(47 reference statements)
2
12
0
Order By: Relevance
“…In turn, this triggers Ca 2+ release from the endoplasmic reticulum, resulting in an increased concentration of cytosolic Ca 2+ and further activation of PKC (24,25). PKC is one of the most important molecules involved in post-membrane signaling transduction and participates in a crucial cell-signaling transduction pathway for atherosclerosis (26). .05 vs. TNF-α group.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this triggers Ca 2+ release from the endoplasmic reticulum, resulting in an increased concentration of cytosolic Ca 2+ and further activation of PKC (24,25). PKC is one of the most important molecules involved in post-membrane signaling transduction and participates in a crucial cell-signaling transduction pathway for atherosclerosis (26). .05 vs. TNF-α group.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial cells also have been suspected as primary targets in the process of inorganic arsenic-induced vascular diseases (Engle et al, 1994). A recent study has demonstrated that iAs III causes a loss of endothelial monolayer integrity (Pereira et al, 2007). Since vascular endothelial cell damage is an important event in the pathogenesis of atherosclerosis (Munro and Cotran, 1988;Ross, 1993), protection of the pathologic changes in vascular endothelial cells could contribute to the prevention of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Direct and indirect effects of arsenic exposure on ischemic stroke risk are biologically plausible further supporting the hypothesis that arsenic is associated with stroke. Arsenic may directly accelerate atherosclerosis by inducing endothelial dysfunction because arsenic disrupts endothelial monolayer integrity, 10 increases production of reactive oxygen 28 and nitrogen 29 species contributing to cytotoxicity, increases inflammatory markers, 29 and disrupts the intravascular matrix. 7 Arsenic may also increase stroke risk through platelet-mediated effects because arsenic increases platelet aggregation and the formation of arterial thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…6 At concentrations Ͼ300 g/L, health risks from arsenic are unequivocal; however, evaluating risks from chronic, low-level exposures (Ͻ100 g/L) has generated much debate. 7 Mechanistic and human studies have suggested a role for arsenic in atherosclerosis, 8 -11 perhaps through decreases in the vascular matrix, 8 disruption of endothelial integrity, 10 and enhanced platelet aggregation. 9 Roughly 85% of strokes in the United States are ischemic in nature with the primary underlying condition being atherosclerosis.…”
mentioning
confidence: 99%